Death Anxiety and Defense Mechanism as Seen in Adam Silvera’s The First to Die at the End: A Psychoanalytic Reading - Nurainina Berliani Natanda (Lexicon, 2026)
This research examines death anxiety and defense mechanisms experienced by Valentino Prince in The First to Die at the End and the influence of defense mechanisms on his actions and interactions with others while dealing with his imminent death. This research uses a qualitative approach with a psychoanalytic perspective. The researcher applies Robert Langs’ death anxiety, Anna Freud’s defense mechanisms, and George E. Vaillant's hierarchical defense mechanisms theory. The findings indicate that Valentino experiences two types of death anxiety: predatory and existential death anxiety. In response, Valentino reveals four types of defense mechanisms: 1) denial, 2) intellectualization, 3) reaction formation, and 4) sublimation. The other result shows that sublimation is the most adaptive defense mechanism, as it allows Valentino to channel his anxiety into meaningful actions. Thus, all of the defense mechanisms used by Valentino are mainly adaptive, enabling him to confront his imminent death while maintaining emotional stability and making purposeful experiences during his final day, although some of the defenses give maladaptive outcomes. This research contributes to comprehending the psychological complexities of dealing with mortality through the lens of psychoanalysis.